PENGGUNAAN MULTIMEDIA PEMBELAJARAN INTERAKTIF DENGAN I-SPRING PRESENTER UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN - Rusyani, Herlin; Hermana, Dody; Hamdani, Nizar Alam (PEDAGOGIA, 2016)
The research is to find out the effectiveness of using interactive learning multimedia with I-SPRING PRESENTER to improve motivation and civics education learning outcome in STIkes Karsa Husada Garut.The taken population is nursing students, Diploma III Grade I, STIkes Karsa Husada Garut. The specimen are 1 B grade as control class with 38 students and 1 C grade as experiment class with 38 students.The research methodology used in this research is experiment research method with quantitative approach. The used experiment method form is by Quasi Experimental design with Non equivalent Control Group Design form. Data collection instrument for learning motivation uses scale with five choice answer opinions, while learning outcome is done by test. The research result data are previously done by making normality test. Data analysis uses T test with SPSS (Statistical Product and Service Solution) software version 17 and MS.excel 2010.The obtained research results are: 1. Motivation before using learning multimedia is low-value, however by interactive learning multimedia, it is high-value, so there is learning motivation improvement. 2. Learning outcome of experiment group is high, while control group is fair. Those show that students’ learning outcome improvement using interactive learning multimedia is better than those using conventional learning.Key words: Interactive Learning Multimedia, Motivation, Learning Outcome